Peningkatan Pengetahuan Tentang Kesehatan Paru Dan Polusi Udara Pada Pengemudi Ojek Online - Rita Khairani; Mustika Anggiane; Dyah Ayu Woro; Henie Widowati (JURNAL ABDIMAS KESEHATAN TERPADU, 2023)
The most common source of air pollution in urban areas comes from motor vehicles, which account for 70% of air pollution. Indoor or outdoor air pollution can cause illness and even death. The highest mortality is in countries with low to middle income, namely in Southeast Asia and the Western Pacific region with 3.3 million deaths caused by indoor air pollution and 2.6 million deaths caused by outdoor air pollution. Online ojek drivers are a group of workers who are vulnerable to exposure to air pollution as well as exposure to cigarette smoke. So far no studies or counseling activities have been found, especially regarding knowledge about lung health in online ojek drivers, so it is still necessary to hold health service activities in the form of education about the importance of lung health. The activity was held on Saturday, November 12, 2022 at the Faculty of Medicine Universitas Trisakti, attended by 30 online ojek drivers in the West Jakarta area. The results obtained through this activity are the increased knowledge of participants about the importance of maintaining lung health as evidenced by the increase in post test scores after attending counseling. The conclusion of this activity went well supported by all related parties starting from the institution, the implementation team and partners who actively participated. Suggestions that we can provide by conducting periodic evaluations of behavior change after receiving counseling.